A precise optical transmission spectrum of the inflated exoplanet WASP-52b - Louden, T; Wheatley, PJ; Irwin, PGJ; Kirk, J; Skillen, I (Oxford University Press, 2017)
We have measured a precise optical transmission spectrum forWASP-52b, a highly inflated hot Jupiter with an equilibrium temperature of 1300 K. Two transits of the planet were observed spectroscopically at low resolution with the auxiliary-port camera on the William Herschel Telescope, covering a wide range of 4000-8750 Å. We use a Gaussian process approach to model the correlated noise in the multiwavelength light curves, resulting in a high precision relative transmission spectrum with errors of the order of a pressure scaleheight.We attempted to fit a variety of different representative model atmospheres to the transmission spectrum, but did not find a satisfactory match to the entire spectral range. For the majority of the covered wavelength range (4000-7750 Å), the spectrum is flat, and can be explained by an optically thick and grey cloud layer at 0.1 mbar, but this is inconsistent with a slightly deeper transit at wavelengths > 7750 Å.We were not able to find an obvious systematic source for this feature, so this opacity may be the result of an additional unknown absorber.